Impact of Housekeeping Services to Guests in Hotel Accommodation, Tri-Cities in Cebu, Philippines (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Housekeeping services are a critical component of the hospitality industry, especially in deluxe-class hotels, where guest expectations are exceptionally high. These services directly influence the quality of a guest’s stay, affecting both their overall experience and satisfaction. In a luxury hotel setting, cleanliness, comfort, and attention to detail are paramount, and housekeeping plays a pivotal role in maintaining these standards. The efficiency, professionalism, and consistency of housekeeping services can significantly impact a guest's perception of the hotel and contribute to their overall satisfaction. This is particularly important in deluxe-class hotels, where the competition for high-end clientele is fierce, and guest satisfaction is a key factor in ensuring repeat visits and positive reviews.This study utilized the descriptive-correlational method of research using a researcher-made survey checklist questionnaire, which includes the demographic profile of the respondents in terms of age, gender, civil status, nationality, and purpose of stay; and the impact of the housekeeping services to guest in a hotel accommodation in terms of cleanliness, room presentation, timeliness of the service, and staff professionalism.This study utilized a random sampling of ten (10) respondents per selected six (6) hotels in Cebu, and a total of fifty (60) respondents who will take part in this study. A researcher-made survey questionnaire will be used to administer the conduct and distribution as a means to gather the facts and information of this study the instrument tool is composed of three (3) parts; the first part is the profile of the respondents where the respondents utilized the checklist questionnaires and the second part is the impact of the housekeeping services on the guest satisfaction as rated by the respondents where utilized also the checklist questionnaire in accordance to the rating scales and categorical responses of 4-Highl Impact, 3-Moderate Impact, 2-Less Impact, and 1-No Impact, and the third part is the problems encountered by the respondents were also rated by them. The statistical tools that will be used in this study are frequency count and percent, weighted mean and ranking, along with inferential statistics including Chi-Square, Analysis of Variance, or t-test to comprehensively test the hypotheses and significant differences of the variables of the study. The findings of the study will serve as the basis for a proposed action plan.